Design and Fabrication of a Body-Powered 3D-Printed Finger Prosthesis for Trans-Phalangeal Amputation - Desinta Dewi Ramadani; Farid Triawan; Muslimin (Politeknik Negeri Medan, 2026)
High cost and ongoing maintenance requirements keep many finger amputees in underdeveloped nations from accessing prosthetic devices. The most prevalent upper-limb amputation, trans-phalangeal amputation (accounting for about 78% of cases), is addressed in this paper as requiring a low-cost, effective finger prosthesis. Using a single degree-of-freedom (1-DOF) connection mechanism and additive manufacturing, a body-powered prosthetic finger was designed and built. Aiming to restore fundamental grip function, the device is customisable to the user's hand size. Defining user needs (affordability, simplicity of use, comfort), investigating several four-bar linkage designs, and kinematic analysis optimisation of the mechanism constituted the design process. Using fused deposition modelling (FDM) 3D printing with polylactic acid (PLA), a prototype was created and evaluated for range of motion and load capacity. With a straightforward tether actuation by the remaining finger, the last prosthesis effectively simulates natural finger bending from extended to curled states. Lightweight and easy to wear, it survived lifting items up to a particular weight—on the order of a few kilograms—before mechanical slip occurred. The 3D-printed finger prosthesis shows that a low-cost, body-powered device can restore fundamental grasp abilities for trans-phalangeal amputees. Further studies will include user trials to assess long-term comfort and function as well as material enhancements for durability.